Alterations in the steroid biosynthetic pathways in the human prefrontal cortex in mood disorders: A post‐mortem study. (17th August 2017) - Qi, Xin‐Rui; Luchetti, Sabina; Verwer, Ronald W. H.; Sluiter, Arja A.; Mason, Matthew R. J.; Zhou, Jiang‐Ning; Swaab, Dick F.
Abstract: Altered levels of steroids have been reported in the brain, cerebral spinal fluid and plasma of patients with mood disorders. Neuroimaging studies have reported both functional and structural alterations in mood disorders, for instance in the anterior cingulate cortex (ACC) and dorsolateral prefrontal cortex (DLPFC). In order to determine whether the endogenous production of steroids is altered in the ACC and DLPFC of patients with major depressive disorder (MDD) or bipolar disorder (BPD), quantitative real‐time PCR was performed to detect mRNA expression level of key enzymes in the steroid biosynthetic pathways. In MDD, a significant decrease in mRNA level of cytochrome P450 17A1 (CYP17A1, synthesizing C19 ketosteroids) in the ACC and a significant increase in mRNA levels of hydroxysteroid sulfotransferase 2A1 [SULT2A1, catalyzing the sulfate conjugation of dehydroepiandrosterone (DHEA)] were observed in the DLPFC, suggesting alterations in DHEA and its sulfate metabolite DHEAS levels. Decreased intensity and distribution of CYP17A1 immunohistochemical staining was found in the ACC of MDD patients. Interestingly, there was a significant positive correlation between the mRNA levels of CYP17A1 and tyrosine‐related kinase B (TrkB) full length isoform. In a unique post‐mortem human brain slice culture paradigm, BDNF mRNA expression was found to be significantly increased following incubation with DHEA. Together, these data indicate a close relationship between DHEA and BDNF‐TrkB pathways in depression. Furthermore, in the DLPFC, higher mRNA levels of 11β‐hydroxysteroid dehydrogenase‐1 (HSD11B1, reducing cortisone to the active hormone cortisol) and steroidogenic acute regulatory protein (STAR, facilitating the shuttle of cholesterol through the intermembrane space) were found in the MDD patients and BPD patients, respectively. In conclusion, this study suggests the presence of a disturbance in the endogenous synthesis of DHEA and DHEAS in mood disorders, which has a close relationship with BDNF‐TrkB signaling.